DIFFERENCES IN MATHEMATICS LEARNING OUTCOMES OF STUDENTS WHO ACQUIRED COLLABORATIVE LEARNING AND CONVENTIONAL LEARNING ON CUBE AND BEAM DISCOURSE IN CLASS VIII SMP N 16 BENGKULU CITY - Jumiati Siska (EDU-MAT: Jurnal Pendidikan Matematika, 2017)
Abstract. This research was motivated from observation during my apprentice where the teachers were still using conventional learning model in class. In this rapidly changing era, students will find it difficult to face the advances in education. For that reason, we need a model of learning that can make students to be more active in learning, so that their ability can thrive well. Collaborative learning is one of the learning models using students’ cooperation as its main core and demanding the students activeness in solving problems especially math problems. Hopefully it can improve students' understanding and make them get good learning outcomes. The main problem of this research was to find whether there are differences in mathematics learning outcomes of students who acquired collaborative learning and those who acquired conventional learning on the subject of cubes and beams. The type of research used was Pseudo Experiments. This research was conducted in class VIII SMP 16 Kota Bengkulu from April 5 to April 27, 2016.  Data collection was done with learning result test. The test was conducted before and after learning. The data obtained were analyzed by statistic Z test. From the result of the research, it was found that there were differences of mathematics learning results of students who acquired collabotive learning versus those who acquired conventional learning. Collaborative learning was able to make students more active in learning so that their understanding to the material seemed to be better. For further research, it is recommended that the subject be expanded to other classes, try other lessons that can improve students' mathematics learning outcomes and it is better that improving the students’ learning outcomes be supported with facilities and other supporting factors. Keywords:  Model, Differences, Collaborative Learning, Conventional Learning